Evaluation of the knowledge of students concerning sexually transmitted infections in Bavaria/Germany (a cross‐sectional study). (8th January 2022) - Rummel, Marcel; Clanner‐Engelshofen, Benjamin M.; Nellessen, Tobias; Zippel, Stefan; Schuster, Barbara; French, Lars E.; Reinholz, Markus
Summary: Background and objectives: Despite numerous information sources and campaigns on sexually transmitted infections (STIs), there has been an increase in STIs in Germany in recent years. The aim was to evaluate the awareness and knowledge level among young students in Bavaria/Germany for STIs with a focus on human papilloma viruses (HPV). Methods: In a cross‐sectional survey rendered completely and irreversibly anonymous, a total of 4, 100 students from Bavaria between the ages of 12 and 17 were interviewed using a multiple choice questionnaire about their knowledge and awareness of STI, on the basis of gender, school education and preventive youth health examinations that had taken place. Results: A total of 3, 834 questionnaires were included in the data analysis. Interestingly, the awareness level for HPV is remarkably lower compared to other STIs. Girls and adolescents who had already taken preventive youth health examinations showed a higher knowledge of STIs on average. Additionally, we could show that adolescents of lower educational levels, such as secondary school students, had the least knowledge. Conclusions: The cross‐sectional study shows that many young people are still insufficiently informed about STIs. The gaps in information and lack of knowledge underline the necessity of intensive and long‐term educational work.